KEKUATAN PEMBUKTIAN SERTIFIKAT SEBAGAI ALAT BUKTI DALAM SIDANG PEMBUKTIAN PERKARA PERDATA DITINJAU MENURUT PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 - Riyanti Riyanti (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACTBased on the research results to date are still many community members who ignore or do not notice proof of land ownership as a strong proof of the right to legal protection , especially in the city of Samarinda . There are many members of the public control of land dozens even hundreds of acres of acres but do not have the right proof . So that legal issues will gradually come , as a result of waiver / registration dilakukannnya not the land as determined by the PP. 24 Year 1997 on Land Registration . Land registration is a series of activities organized by the government with the aim to provide legal certainty and the protection of land rights holders . So the result of a series of activities that is the provision of land registration certificate as a valid proof of copyright strong evidence . This is in accordance with the dictates of Article 19 paragraph ( 1 ) and ( 2 ) BAL . Issuance of the certificate is intended to rights holders can easily prove the physical data and juridical data in it in the physical data contained information on the location , boundaries and vast fields and apartment units that are listed , including information about the existence of a building on it . Juridical data contained in the certificate contains information about the legal status of land parcels and apartment units that are listed right holders and other parties as well as other burdens placed on them . Therefore, a certificate proving a powerful tool that is intended as Article 19 paragraph ( 2 ) letter c BAL . This implies that the trial judge should accept that the data contained in the certificate is correct for the data can not be proven otherwise by others